The Effect of Inflation, BI Rate, Exchange Rate and Standard & Poor's 500 on the Composite Stock Price Index Empirical Study on Manufacturing Companies Listed on the Stock Exchange in 2015-2019 - Albasita, Yulia; Halim, Edyanus Herman; Fitri, Fitri (International Journal of Economic, Business & Applications, 2022)
This study aimed to determine the effect of inflation, the BI rate, the exchange rate, and Standard & Poor's 500 on the Composite Stock Price Index (JCI). The population of this study is all data on the JCI, BI Rate, Inflation, Exchange Rates, and the Standard & Poor's 500 in the 2016–2019 period on the Indonesia Stock Exchange (IDX). The sample for this study was selected by the saturated sampling method within the range of 48 months, starting from January 2016 to December 2019. The analytical tool used in this study was multiple linear regression analysis. The results of this study indicate that inflation, the BI Rate, and the Standard & Poor's 500 have a positive and insignificant effect on the composite stock price index. Furthermore, the exchange rate has a negative and significant effect on the composite stock price index